ANALISIS EFEK GERHANA MATAHARI TOTAL 9 MARET 2016 TERHADAP KANDUNGAN TOTAL ELEKTRON IONOSFER - Afrita Ariani; Usman Malik; Asnawi Husin (Komunikasi Fisika Indonesia, 2020)
Total elektron contant in ionosphere is affected by several fastors, local time, solar aktivities, geomagnetic disturbance, geographical latitude and longitude. This researh aims to observase level variation of total electron contant during solar eclipse over Indonesia on 9 March 2016. We analyzed GPS data from two GPS stations in different locations with different sun observation geographical latitude and longitude, the locations were Sulawesi station (CAMP) and Maluku station (CAMB). The method used in this research, was data interpretation method  computationally, the whole data analyzed using matlab software R2008a. The values of daily TEC range from 20 TECU till 30 TECU. Although the value of TEC when solar total eclipse range from 10n TECU untill 20 TECU. The percentage of decreasing value of TEC when total solar eclipse than the daily value of TEC. Decreasing of TEC value between 20%-40%.